2022
DOI: 10.1155/2022/4942519
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA260 siRNA Accelerates M2 Macrophage Polarization and Alleviates Oxidative Stress via Inhibiting IL28RA Gene Alternative Splicing

Abstract: The macrophage transformation of inflammatory M1 to anti-inflammatory M2 could be promoted by activating PI3K/AKT signaling pathway. In our previous study, it was found that downregulation of lncRNA260 could ameliorate hypoxic cardiomyocyte injury by regulating IL28RA through the activation of PI3K/AKT signaling pathways. It was suggested that lncRNA260 siRNA could promote the macrophages toward M2 polarization by regulating IL28RA. In this study, lncRNA260 siRNA was used to observe its effect on the polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Researchers have confirmed that macrophage polarization mediates oxidative stress by promoting ROS production. Increasing M2 polarization attenuated oxidative stress damage [ 23 ]. Therefore, it is necessary to inhibit oxidative stress and balance M1/M2 polarization to control the development of ARP.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have confirmed that macrophage polarization mediates oxidative stress by promoting ROS production. Increasing M2 polarization attenuated oxidative stress damage [ 23 ]. Therefore, it is necessary to inhibit oxidative stress and balance M1/M2 polarization to control the development of ARP.…”
Section: Discussionmentioning
confidence: 99%
“…NC group: BMDM were cultured with DMEM containing M-CSF (20 ng/mL); SGLT2i group: BMDM were cultured with DMEM containing M-CSF (20 ng/mL) and dagliflozin (1 µM). 19 BMDMs were subsequently used for PKH26 dye labeling, cell transplantation, and flow cytometry analysis.…”
Section: Methodsmentioning
confidence: 99%
“…lncRNAs are non-protein-coding RNAs with a length of more than 200 nucleotides, which are involved in cell differentiation and proliferation, cycle regulation, tumor development, and other pathophysiological processes. Macrophage polarization is also affected by some lncRNAs, such as ANCR, Mirt2, HITT, GAS5, and RN7S [80][81][82][83][84][85][86], as shown in Table 3.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%